Multivariate muti-level non-linear mixed-effect models and their application to the modeling of drug-concentration time curves - Mauff, Katya (Department of Statistical Sciences, 2014)
This thesis discusses the techniques involved in the fitting of nonlinear mixed effect (NLME) models. In particular, it looks at the application of these techniques to the analysis of concentration-time data for the aforementioned antimalarial compounds, and details the necessary extensions to the basic modeling process that were required in order to accommodate multiple responses and multiple observation phases (pregnant and postpartum).